PENGEMBANGAN MODUL AJAR BERBASIS BUDAYA JAWA UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIS SISWA PADA MATERI BANGUN DATAR DI KELAS IV UPT SPF SD NEGERI 101921 BERINGIN - Safitri, Devi; Devi Safitri, Ahmad Landong; Mawarni, Elsa; Khairunisa, Novia Futty; Nuraminah, Nuraminah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Creating an understanding of complex concepts certainly requires an appropriate model to support student stimuli in thinking scientifically, particularly in mathematics learning. Ethnomathematics-based learning is a pedagogical approach that relates to the real world by applying ethnomathematics in the classroom learning process. The implementation of this method is carried out by integrating local cultural elements into the learning materials. This research aims to investigate students' responses to Javanese culture-based teaching modules and to determine the validity, practicality, and effectiveness of Javanese culture-based teaching modules in improving students' mathematical learning outcomes. This type of research employs the Research and Development (R&D) method with the ADDIE model. The results of the study show that the average validation assessment score from media experts is 4.5%, categorized as